Integrasi Nilai-nilai Islam dalam Pembelajaran Bahasa Inggris untuk Pengembangan Soft Skill Kewirausahaan: Studi di Politeknik Balekambang Jepara - Muhammad Ali Subkan; Ahmad Mubais; Rasyiid Yoga Pradita; Purwati Purwati (Jurnal Pendidikan dan Sastra Inggris, 2025)
English language instruction in higher education, particularly within vocational institutions based on Islamic boarding schools (pesantren), holds significant potential not only for developing linguistic competence but also for shaping students’ character and entrepreneurial soft skills. This study aims to describe the current state of English language teaching in the context of entrepreneurial soft skill development, identify relevant Islamic values to be integrated, and formulate strategies for integrating those values into the learning process. This research employed a qualitative descriptive approach using a case study method at Politeknik Balekambang Jepara. Data were collected through in-depth interviews, classroom observations, and document analysis, then analyzed thematically. The results show that English teaching remains focused on linguistic aspects, with limited integration of Islamic values and entrepreneurial soft skill development. Relevant Islamic values identified include shiddiq (honesty), amanah (responsibility), tabligh (communicativeness), and fathanah (intelligence/innovation). Recommended integration strategies include the use of Islamic-contextual learning materials, project-based learning with entrepreneurship themes, interdisciplinary collaboration, and value reflection during assessments. This study contributes to the development of a holistic learning model based on values and skills.